The Effect of Online Reporting About Paid Vaccine on Public Trust in Government - Haryadi Mujianto; Iis Zilfah Adnan; Nurul Syamsiah (LPPM Stikosa - AWS, 2023)
This research was motivated by public unrest with the news about paid vaccines, where the beginning of this vaccine was not charged at any cost. The purpose of this study is to measure how much influence paid vaccine news on online media has on public trust in the government. The research method used is descriptive research to describe the variables to be explained and also in the analysis of how much influence the variables have. The approach used is a quantative approach with data collection techniques, namely by using questionnaires that have been tested for validity and reliability, the subjects of this study are the people of Garut Regency as many as 100 respondents, statistical data analysis using regression analysis, determination coefficient analysis and hypothesis testing. The results showed based on the F test in table VII.1, the calculated F value is 51.870 with a value significance of 0.000 then the hypothesis H0 is rejected and H1 is accepted. This means there is influence between online reporting about paid vaccines and public trust that the Rioting of News in Online Media Regarding Paid Vaccines Against Public Trust in the Government had a significant influence. The influence of Online Media Reports on Paid Vaccines on Public Trust is quite strong. And there is a strong influence on the community from the news of this Paid Vaccine.